If a Tree Falls: Business Students Learning Active Citizenship from Environmentalists - Helen Kopnina; Maria Helena Saari (MDPI AG, 2019)
This article presents and discusses student assignments reflecting on the documentary film If a Tree Falls, written as part of the Business Ethics and Sustainability course at The Hague University of Applied Sciences. This article follows two lines of inquiry. First, it challenges mainstream environmental education, supporting critical pedagogy and ecopedagogy. These pedagogies, which advocate pedagogy for radical change, offer a distinct and valuable contribution to sustainability education, enabling students to critically examine normative assumptions, and learn about ethical relativity, and citizenship engagement from environmentalists. The discussion of "lessons of radical environmentalism" is pertinent to the question of what types of actions are likely to achieve the widely acceptable long-term societal change. While this article focuses on student reflection on a film about radical environmentalism, this article also discusses many forms of activism and raises the question of what can be considered effective activism and active citizenship in the context of the philosophy of (environmental or sustainability) education in connection didactics and curriculum studies. Second, this article argues for the need for reformed democracy and inclusive pluralism that recognizes the needs of nonhuman species, ecocentrism, and deep ecology. The connection between these two purposes is expressed in the design of the student assignment: It is described as a case study, which employs critical pedagogy and ecopedagogy.